THE EXISTENCE OF TADUT ART IN MUARA DUA VILLAGE, LAHAT: A STUDY OF FACTORS AND PRESERVATION MECHANISMS - Widia Putri (Journal of Education and Teaching Learning, 2026)
This study aims to examine the existence of the Tadut art form among the Muara Dua community in Pagar Gunung District, Lahat Regency, as well as to analyze the factors influencing its sustainability and preservation mechanisms. Tadut is a traditional oral literature of the Besemah people that is rich in Islamic values and historically served as a vital medium for religious learning when access to literacy was limited. This study employs a qualitative approach with a descriptive method. Data were collected through participant observation, in-depth interviews with three key informants selected via purposive sampling, and documentary studies. The results indicate that Tadut was introduced to Muara Dua in 1657 by Ki Haji Mahmud as a medium for teaching Islam. During its golden era (1657–1970), Tadut played a central role in Islamic dawah (prosetylization) and education; however, after the 1970s, its function shifted into a ceremonial art performed during tahlilan (mourning rituals) and wedding ceremonies. The existence of Tadut is influenced by social, aesthetic, functional, as well as knowledge and educational factors. Meanwhile, the primary inhibiting factors include socio-cultural changes, shifts in aesthetic values, the loss of its primary function, lack of documentation, and weak regeneration. Preservation efforts undertaken by the community and the local Cultural Heritage Foundation remain sporadic and have not been systematically structured. This study concludes that although Tadut still exists, its sustainability heavily depends on role revitalization, adaptive innovation, and active support from all stakeholders.